Effect of positive microbiological testing on antibiotic de-escalation and outcomes in community-acquired pneumonia: a propensity score analysis. (December 2022) - Abelenda-Alonso, Gabriela; Rombauts, Alexander; Gudiol, Carlota; García-Lerma, Esther; Pallarés, Natalia; Ardanuy, Carmen; Calatayud, Laura; Niubó, Jordi; Tebé, Cristian; Carratalà, Jordi
Abstract: Objectives: The usefulness of routine microbiological testing for rationalising antibiotic use in hospitalised patients with community-acquired pneumonia (CAP) continues to be a subject of debate. We aim to determine the effect of positive microbiological testing on antimicrobial de-escalation and clinical outcomes in CAP. Methods: A retrospective analysis of a prospectively collected cohort of non-immunosuppressed adults hospitalised with CAP was performed. The primary study outcome was antimicrobial de-escalation. Secondary outcomes included 30-day case-fatality rate, adverse events, and CAP recurrence. Adjustment for confounders was performed by inverse probability weighting propensity score, logistic regression, and cause-specific Cox model. Results: Of 3677 patients with CAP, 1924 (52.3%) had any positive microbiological test. Antimicrobial de-escalation was performed in 648/1924 (33.7%) of patients with positive microbiological testing and in 179/1753 (10.2%) of those with non-positive results. When propensity score was entered into the multivariate analysis, positive microbiological testing (adjusted OR (AOR)], 2.59; 1.96–3.41) and clinical stability at day 3 (AOR 1.87; 1.45–2.10) were two of the main factors independently associated with antimicrobial de-escalation. After applying an adjusted cause-specific Cox model, antimicrobial de-escalation was not associated with a higher 30-day case-fatality rate (adjusted hazard ratio (AHR), 0.44 (95% CI, 0.14–1.43)), higher frequency of adverse events (AHR, 0.77 (95% CI, 0.53–1.12)), or CAP recurrence (AHR, 0.65 (95% CI, 0.35–1.14)). Discussion: Antimicrobial de-escalation was more often performed in hospitalised patients with CAP who had positive microbiological tests than in those with non-positive results, and it did not adversely affect relevant clinical outcomes.